CETOSE PÓS-PARTO EM VACA LEITEIRA - Silva, Ronaldo Júnior Da; Fraga, Denize Da Rosa; Pereira, Roberta Carneiro Da Fontoura; Beck, Cristiane; Teichmann, Cristiane Elise (Salão do Conhecimento, 2017)
Relato de Caso acompanhado durante o Estágio Clínico I em Medicina Veterinária na UNIJUÍ